Stability Analysis of Fresh Root Yield of Sweetpotato in Southern Ethiopia using GGE Bi-Plot - Gurmu, Fekadu (International Journal of Pure Agricultural Advances, 2017)
The yield performance of sweetpotato is highly influenced by the effect of genotype by environment interaction (G x E) and stability analysis is required before variety release. The objectives of the study were to estimate the magnitude of G x E interactions, to select high yielding and stable elite sweetpotato clones, and to identify the most discriminating and representative test environments in Ethiopia. The study was conducted across six diverse environments in southern Ethiopia in 2014. The locations were Halaba, Kokate, Areka, Arbaminch, Hawassa and Dilla. Twenty five clones (24 elite clones and one check variety) were used for the study and were arranged in a 5 x 5 simple lattice design for field experimentation. Genotype plus Genotype by Environment Interaction (GGE Bi-plot) method was used to study the stability of the clones for fresh root yield. Significant environment, genotype and G x E interaction variances (p < 0.01) were observed for fresh root yield. The magnitude of environment and G x E interaction effect was higher than that of the genotype effect. Three clones, G1 (Ukrewe x Ejumula-10), G6 (Resisto x Ejumula-7) and G20 (Ejumula x PIPI-10) were identified as stable and relatively high yielding genotypes. The mean root yields of the three clones were 25.1, 26.9 and 25.5 t ha-1, respectively for G1, G6 and G20. Accordingly, the above three elite clones were selected for ultimate evaluation and recommendations. Among the test locations, the highest and stable mean fresh root yield of 37.1 t ha-1 was recorded at Arbaminch. Therefore, Arbaminch was identified as the best environment for sweetpotato production in southern Ethiopia. The study revealed the possibility of breeding sweetpotato varieties for high yielding and stable clones that have wide adaptation in southern and similar agro-ecologies in Ethiopia.